Effect of PEEK Particles on Physiomechanical Behavior of Carbon/Epoxy Composite - Muhammad Muslim Rehman; Khubab Shaker; Yasir Nawab (International Journal of Polymer Science)
The inherently brittle nature and the susceptibility to impact damage hinder the use of carbon/epoxy composite in some areas. In this study, poly ether ether ketone (PEEK) microparticles were incorporated to increase the resistance to delamination and interlaminar fracture toughness. A hand lay-up technique followed by compression molding was used to fabricate composite. The influence of PEEK particles was evaluated by tensile, flexural, short beam shear (SBS), compression, and Charpy impact test. The Barcol hardness, density, fiber volume fraction, and void content were also determined. According to the result, a maximum improvement in the tensile and flexural strength was observed for 2% incorporation of PEEK particles. However, there is downturn found in the flexural modulus. Moreover, a notable increment in the matrix-dominated properties (short beam shear, compression, and Charpy impact strength) was found with the addition of the PEEK particles.